Peningkatan Penggunaan Social Learning Network Bagi Siswa-Siswi SMP Negeri 2 Syamtalira Aron Kab. Aceh Utara - Juni Ahyar; Ikramuddin Ikramuddin; T. Edyansyah; Rizka Astuti; Maqfiratun Misla (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Today the development of the internet is increasing rapidly and has penetrated into several fields, including the field of education. Learning media also develops and creates a Social Learning Network. Edmodo is an online learning medium that combines several Learning Management Systems and Social Network features into a Social Learning Network specifically made for educational purposes. To obtain an effective learning process, teachers and students must have innovative and interesting learning media, this is what is experienced by SMP Negeri 2 Syamtalira Aron North Aceh Regency. Teachers of SMP Negeri 2 Syamtalira Aron North Aceh Regency have carried out training on increasing the use of Edmodo learning media, but students still have not used social network-based learning media. This is the background for the service team to provide training on